IMPACT OF UNFAVORABLE FACTORS OF PRODUCTION AND ENVIRONMENT ON THE POPULATION LIVING CLOSE TO INDUSTRIAL ENTERPRISES (LITERATURE REVIEW) - Красильникова, Полина Леонидовна; Панев, Николай Иванович; Коротенко, Ольга Юрьевна (Medicine in Kuzbass, 2024)
The life of contemporary person living in megacities, industrial production, pollution of atmospheric air, water and soil leads to the development of a new class of diseases caused by the toxic effect of various production factors on all organs and systems. Unlike viral or bacterial infections, epidemics of which in previous centuries claimed lives of millions of people, occupational diseases develop gradually, affect not only individual organs and systems, but also affect human genetics. In recent decades, the problems of occupational diseases have received much attention.Materials and methods. Based on the analysis of PLOS ONE, Pub Med, Google Scholar, CyberLeninka databases, a review of scientific literature on the prevalence, pathogenesis, morphology of diseases caused by the effect of coal-rock dust, vibration, electromagnetic and electric fields on humans was conducted.Results. The conducted analysis revealed various types of organ and system damage against the background of exposure to solid particles of coal-rock dust, vibration and other risk factors. The development of chronic inflammation during the ingestion of solid particles 0.1 microns in size provokes a cascade of reactions leading to degenerative, fibroplastic and neoplastic processes of the respiratory organs, cardiovascular system, digestion, and blood. The pathological effect can be observed not only in persons employed in harmful production, but also in inhabitants of industrial regions, including women of reproductive age, children and adolescents.Conclusion. Early detection of risk factors, reduction of their toxic effect on professional employees and the population living in a disadvantaged area is necessary to preserve the health of the nation and future generations.
Keywords: occupational medicine; occupational risk factors; diseases of internal organs; coal dust